Structurally different anabolic androgenic steroids reduce neurite outgrowth and neuronal viability in primary rat cortical cell cultures. Issue 210 (June 2021) - Zelleroth, Sofia; Nylander, Erik; Örtenblad, Axel; Stam, Frida; Nyberg, Fred; Grönbladh, Alfhild; Hallberg, Mathias
Graphical abstract: Highlights: Structurally different anabolic steroids exhibit diverse neurotoxic properties. Trenbolone, testosterone, and nandrolone reduce neurite outgrowth. Trenbolone downregulates the Tubb3 gene expression and decreases cell viability. Altered neurons may contribute to the mental health problems seen in AAS users. Abstract: The illicit use of anabolic androgenic steroids (AAS) among adolescents and young adults is a major concern due to the unknown and unpredictable impact of AAS on the developing brain and the consequences of this on mental health, cognitive function and behaviour. The present study aimed to investigate the effects of supra-physiological doses of four structurally different AAS (testosterone, nandrolone, stanozolol and trenbolone) on neurite development and cell viability using an in vitro model of immature primary rat cortical cell cultures. A high-throughput screening image-based approach, measuring the neurite length and number of neurons, was used for the analysis of neurite outgrowth. In addition, cell viability and expression of the Tubb3 gene (encoding the protein beta-III tubulin) were investigated. Testosterone, nandrolone, and trenbolone elicited adverse effects on neurite outgrowth as deduced from an observed reduced neurite length per neuron. Trenbolone was the only AAS that reduced the cell viability as indicated by a decreased number of neurons and declined mitochondrial function. Moreover, trenbolone downregulated the Tubb3 mRNA expression. The adverse impact on neurite development was neither inhibited nor supressed by the selective androgen receptor (AR) antagonist, flutamide, suggesting that the observed effects result from another mechanism or mechanisms of action that are operating apart from AR activation. The results demonstrate a possible AAS-induced detrimental effect on neuronal development and regenerative functions. An impact on these events, that are essential mechanisms for maintaining normal brain function, could possibly contribute to behavioural alterations seen in AAS users.